2020
DOI: 10.1590/1678-7757-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

Gingival fibroblasts behavior on bioactive zirconia and titanium dental implant surfaces produced by a functionally graded technique

Abstract: Adding a biological apatite layer to the implant surface enhances bone healing around the implant. Objective This study aimed to characterize the mechanical properties and test human gingival fibroblasts behavior in contact with Zirconia and Titanium bioactive-modified implant materials. Methodology 6 groups were considered: Titanium (Ti6Al4V), Ti6Al4V with 5% HA and 5% ßTCP, Zirconia (YTZP), YTZP with 5% HA and 5% ßTCP. For each group, we produced discs us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(57 reference statements)
0
9
0
Order By: Relevance
“… Before: 78.31°; 0.05 ± 0.01 μm [ 118 ] After: 43.71° 13 Y-TZP containing 5% HA or 5% β-TCP Bioactive modified HGFs in vitro HGF adhesion, viability, and proliferation were decreased. Before: 70.59°; 1.45–1.86 μm [ 121 ] After: 70.82°, 65.04° 14 Y-TZP; NANOZR Coated with silk fibroin in vitro A silk fibroin electrogel coating had sufficient bonding strength The biocompatibility of zirconia was improved. [ 132 ] 15 ZrO 2 Coated with polydopamine (PDA) HGFs in vitro Cell attachment and proliferation were increased; Bacterial adhesion was reduced.…”
Section: Surface Modification Of Zirconia Abutmentsmentioning
confidence: 99%
See 1 more Smart Citation
“… Before: 78.31°; 0.05 ± 0.01 μm [ 118 ] After: 43.71° 13 Y-TZP containing 5% HA or 5% β-TCP Bioactive modified HGFs in vitro HGF adhesion, viability, and proliferation were decreased. Before: 70.59°; 1.45–1.86 μm [ 121 ] After: 70.82°, 65.04° 14 Y-TZP; NANOZR Coated with silk fibroin in vitro A silk fibroin electrogel coating had sufficient bonding strength The biocompatibility of zirconia was improved. [ 132 ] 15 ZrO 2 Coated with polydopamine (PDA) HGFs in vitro Cell attachment and proliferation were increased; Bacterial adhesion was reduced.…”
Section: Surface Modification Of Zirconia Abutmentsmentioning
confidence: 99%
“…Bionic surface coatings, such as hydroxyapatite (HA), β-tricalcium phosphate (β-TCP), collagen and chitosan, may promote soft tissue formation around zirconia abutments. However, soft tissues reacted inconsistently towards these coatings [ 46 , [119] , [120] , [121] , [122] , [123] , [124] ] and they gave desirable results on titanium surfaces but not on zirconia [ 121 ]. Biomimetics, silk protein and polydopamine (PDA), have also been investigated to construct surface coatings [ 125 ].…”
Section: Surface Modification Of Zirconia Abutmentsmentioning
confidence: 99%
“…The biological responses performed after the placement of a biomaterial in the oral environment are very important for tissues where there is a need for healing [ 3 , 12 , 13 ]. Surface modifications, functionalization of ZrO 2 , as well as innovations in the base-material can induce individualized cellular responses promoting a better performance of the device once it is implanted [ 9 , 12 , 17 , 70 ]. As a result, intraosseous implants, components for implants and oral prostheses made from ZrO 2 have attracted the attention of researchers and clinicians due to their biocompatibility properties ( Table 2 ).…”
Section: Biological Responsesmentioning
confidence: 99%
“…Rottmar et al demonstrated that zirconia surfaces had the best performance with regards to fibrinogen adsorption and thrombogenicity [ 15 ]. Furthermore, reports prove zirconia to have an advantage in terms of biological properties with soft peri-implant tissues thereby modulating fibers and cell attachment and behavior with greater effectiveness and biocompatibility [ 16 , 17 ]. Along with the properties mentioned above, zirconia has a low surface energy [ 18 , 19 ], therefore it retains very low amounts of plaque and consequently has less bacterial colonization on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, yttria-stabilized polycrystalline tetragonal zirconia (YTZP) is the most popular because of its mechanical properties and similarity to titanium. In addition, due to its metal-free properties, coupled with its aesthetic white color and translucency like human teeth, YTZP could be the preferred material for dental implants in the future as an alternative to titanium implants [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%